The gap analysis of pre and post dividend received by members prior and after the splitting of KOPKENEM from RISDA Melaka / Nor Akmar Nor Afandi - Nor Afandi, Nor Akmar (Faculty of Business and Management, 2010)
The purpose of this case study was to know why dividend pre-RISDA versus post-RISDA was different. The amount of dividend was different because the dividend when the cooperative subsidized by RISDA was better than after the cooperative was independent from RISDA. The different amount of dividend also affected the cooperative members. So, they suggested the cooperative to increase the amount of dividend. Then, cooperative must do something to gain higher dividend for their members by doing lot of business. It is because when cooperative gain higher profit they can give higher dividend but if the cooperative failed to gain higher profit the amount of dividend received by members will also decrease. After doing the gap identification between pre-RISDA and post-RISDA can reveal the process to find the solution from the issue of different of divided between pre-RISDA and post RISDA. After doing gaps identification that process helped detect the elements that were contributing to the issue. Finally, suggestions and conclusions had been drawn.